The synthesization of activated carbon from electrocoagulated palm oil mill effluent sludge for wastewater treatment - Farah Amalina, Ishak; Abdul Syukor, Abd Razak; Krishnan, Santhana; Zularisam, Abdul Wahid; Mohd, Nasrullah (Elsevier Ltd, 2023)
The oil palm industry in Malaysia is certainly the one of economic and agricultural drives for the country. Nevertheless, despite the obvious benefits that it possesses, oil palm mill also significantly contributes to environmental degradation. It generates massive amounts of solid waste, wastewater, and air pollution from its production and processing processes. Activated carbon (AC) as an adsorbent has been used widely to remove pollutants in wastewater. Many attempts have been made to produce economically accessible AC. This paper explores the idea of producing an AC, a value-added product, sludge produced from the electrocoagulation process of palm oil mill effluents (POME) through chemical activation. AC has different applications after its discovery as a solid and reliable adsorbent. Its microporous structure, high surface reactivity, and surface area make it versatile and viable for removing pollutants from aqueous solutions. The electrocoagulated sludge-based AC is characterized by its surface characteristics, elemental compositions, surface morphology, and available functional group. To validate the adsorption capacity of electrocoagulated sludge-based AC, textile dye wastewater treatment was carried out to test the efficiency of AC. Results indicate that TSS in textile dye wastewater decreased as the adsorbent dosage increased. The values of TSS removal by AC from H3PO4 activation decreased steadily compared to KOH activation. Meanwhile, the color removal percentage decreased when the dye concentration increased. AC from H3PO4 activation has higher color removal percentage. This shows that AC from H3PO4 activation has better adsorption due to its more extensive surface area. From BET analysis, AC by H3PO4 activation offers a higher surface area, 36.1017 m2/g, compared than KOH activation, 8.9460 m2/g. Extensive surface area has a higher tendency to adsorb contaminations. The findings of this work confirmed the potential use of electrocoagulated sludge-based AC as an alternative and economically adsorbent for effective dye pollution removal in wastewater.